Recurrent melanoma development in a Caucasian female with CDKN2A+ mutation and FAMMM syndrome: A case report. (September 2020) - Gu, Kaien; Velde, Rochelle Van De; Pitz, Marshall; Silver, Shane
Melanoma is a form of skin cancer originating from melanocytes that has an increasing incidence over the past few decades. From 1992 to 2010, the overall incidence of melanoma was 12.29 cases per 100, 000 person-years in Canada. Approximately 10% of cases are attributed to a hereditary component, with one of the most common being familial atypical multiple mole melanoma syndrome. In this case report, we highlight the atypical case of a middle-aged Caucasian female with familial atypical multiple mole melanoma syndrome, who has developed dozens of primary melanomas over the past decade. We highlight the management of her case, as well as the importance of monitoring by multiple other subspecialists given the propensity for the development of alternate malignancies.